Competition drives the evolution of emergent neutrality in the dietary niches of mammalian herbivores. (20th March 2023) - Codron, Daryl; Bousman, C. Britt; Buschke, Falko; Clauss, Marcus; Lewis, Chanel; van der Merwe, Runé; van der Mescht, Aileen; Brink, James S.
Abstract: The coexistence of multiple species competing for a finite set of resources is a widely debated topic in community ecology. Species with strongly overlapping niches are expected to drive each other towards exclusion, but such species may also coexist if they have similar competitive abilities. This compromise can lead to a peculiar pattern of clumped coexistence, where multiple species share similar niches, leaving gaps open in the theoretically available niche space. Large mammal herbivores may be a good example of this, where species' dietary niches clump as either grazers, browsers, or intermediate-feeders, rather than being continuously distributed over the resource gradient. Here, we develop a model of such emergent neutrality amongst species competing for a set of predefined resources each distributed along a finite niche axis. The model is commensurate with stable isotope niches, thus allowing us to compare its predictions with empirical evidence for changes in community niche structure over evolutionary time. We present stable carbon and oxygen isotope evidence for six discontinuous Late Quaternary assemblages from the central interior of South Africa, demonstrating the emergence of a clumped niche structure from an initial pattern of strongly overlapping diets. We show that species tend to cluster on parts of the niche axis where resource availability is highest, mirroring the proliferation of grazer species as landscapes became more grass-dominated. However, the presence of competition means that species' niches continue to differentiate, explaining the persistence of browser and intermediate-feeder species even in these open, predominantly treeless landscapes. These results highlight that species interactions are a necessary factor for robust inferences about the evolutionary dynamics of palaeocommunities.